The Influence of Financial Literacy on Community Interest in Entrepreneurship in Imogen Products - Wiwin Koni (Global Scientific Publishing, 2023)
This study aims to determine the effect of financial literacy on the entrepreneurial community's interest in Imogen products in Gorontalo. The technique of determining the sample in this study is the Purposive Sampling Technique. Purposive Sampling. The authors use the Lemeshow formula to get the number of samples representing the population because the total population is unknown—a questionnaire data collection method. The data analysis method used in this study includes an instrument feasibility test in the form of a validity and reliability test, a simple regression assumption test in the form of a normality test to see whether the data is normally distributed or not, a linearity test to test whether the relationship between X and Y variables is linear. Because the assumptions are met, a simple linear regression analysis is used. The results of this study indicate that financial literacy has a significant and positive effect on the interest in entrepreneurship. With an effect of 0.651, it means that every increase of one unit of financial literacy will increase interest in entrepreneurship by 0.651
Keywords: contribution; increase; entrepreneurship; assumption